RHBDF1 modulates cisplatin sensitivity of small cell lung cancer through YAP1/Smad2 signaling pathway - Lei Wang; Lishuang Qi; Xiaoyi Huang; Xiao Feng; Junqing Gan; Juxuan Zhang; Yuhui Xi; Shuai Zhang; Qingwei Meng (Heliyon, 2024)
Small cell lung cancer (SCLC) is a fatal tumor type that is prone to drug resistance. In our previous study, we showed that human rhomboid-5 homolog-1 (RHBDF1) was differentially expressed in 5 intrinsic cisplatin-resistant SCLC tissues compared with 5 intrinsic cisplatin-sensitive SCLC tissues by RNA sequencing, which intrigued us. We performed gain- and loss-of-function experiments to investigate RHBDF1 function, bioinformatics analysis, qRT-PCR, western blotting, and immunoprecipitation to elucidate the molecular mechanisms as well as detect RHBDF1 expression in SCLC by immunohistochemistry. We found that RHBDF1 knockdown promoted cell proliferation and cisplatin chemoresistance and inhibited apoptosis in vitro and in vivo. These effects could be reversed by overexpressing RHBDF1 in vitro. Mechanistically, RHBDF1 interacted with YAP1, which increased the phosphorylation of Smad2 and transported Smad2 to the nucleus. Among clinical specimens, the RHBDF1 was a low expression in SCLC and was associated with clinicopathological features and prognosis. We are the first to reveal that RHBDF1 inhibited cell proliferation and promoted cisplatin sensitivity in SCLC and elucidate a novel mechanism through RHBDF1/YAP1/Smad2 signaling pathway which played a crucial role in cisplatin chemosensitivity. Targeting this pathway can be a promising therapeutic strategy for chemotherapy resistance in SCLC.